Geographical analyses of Covid-19’s spreading contagion in the challenge of global health risks: The role of urban and regional planning for risk containment - Murgante, Beniamino; Balletto, Ginevra; Borruso, Giuseppe; Las Casas, Giuseppe; Castiglia, Paolo; Dettori, Marco (TeMA - Journal of Land Use, Mobility and Environment, 2020)
This research develops from a set of basic geographical questions about the outbreak of Covid-19 out of China in Europe. The questions dealt with why and why with such strength Italy has been seriously hit, one of the most important cases in terms of death toll out of Hubei Province and mainland China, in the world, making the country a worldwide study case for epidemic concentration and diffusion. Questions were also related to geographical similarities among the areas hit, and particularly the Po Valley region and Wuhan metropolitan region in Hubei province, and also related to why such a divide of the virus spreading was identified in Italy between Northern and Central and Southern regions and provinces. In order to try to give an answer these questions, authors realized a vast and articulated database of indicators at provincial level in Italy, performing several geographical analyses - ecological approach - based on Spatial autocorrelation and Geographical Weighted Regression, coming to the conclusion that aspects such as land take, pollution can seriously influence the phenomenon and justify a pattern as that observable in Italy. The analyses and observation of the phenomenon also suggests that policies based on urban regeneration, sustainable mobility, green infrastructures, ecosystem services can create a more sustainable scenario able to support the quality of public health.